A inclusão de um aluno com Síndrome de Down nas aulas de Educação Física - Shimoda, Lindomar dos Reis (2020)
This study seeks to understand the practices of inclusion in Physical Education classes for the interaction of a student with Down Syndrome in activities proposed by an intervention research that aimed to teach the contents Popular Games and Games with a